Unveiling soil bacterial ecosystems in andean citrus orchards of Santander, Colombia - Castillo-Villamizar, Genis Andrés; Tapia-Perdomo, Valentina; Maldonado-Pava, Julieth; Santamaría-Gálvis, Pedro; Sayavedra, Lizbeth; Hernandez-Torres, Jorge; Puentes-Cala, Edinson (Frontiers in Ecology and Evolution, 2024)
Citrus cultivation is vital to global agriculture, necessitating a comprehensive understanding of the soil microbiome's diversity for sustainable practices. This study provides initial insights into the bacteriome in citrus crops in Santander, Colombia, employing a holistic approach combining culture-based techniques, sequencing methods, and bioinformatics analyses. The study explores organic and non-organic cultivation systems, revealing statistically significant differences in bacterial community composition between both practices. In general, the communities are dominated by members of the Actinobacteria and Proteobacteria, along with bacterial orders Gaiellales and Burkholderiales, all contributing to intricate ecological processes. Culture-based methods aided in the isolation of potential biotechnologically relevant strains. Among them, strain CP102 showed a pronounced carboxymethylcellulose (CMC) degradation capacity. Genetic analysis of the isolate resulted in the generation of the first closed genome of a member of the species Enterobacter soli and identified an unreported 109 kb plasmid. Further genomic examination revealed genes potentially associated with cellulose degradation in this species, which provides the isolate with biotechnological potential. This research significantly advances the global understanding of citrus-associated bacteriomes, shaping future agricultural practices and promoting the development of sustainable bioproducts.